Labour Regulation and Development (Edward Elgar Publishing, 2023)
This book is an exploration of arguments about the economic and social effects of the regulation of labour, and whether it is likely to be helpful or harmful to development. Authored by contributors from a variety of fields, primarily legal as well as development studies, economics and regulatory studies, the book presents both empirical and theoretical analyses of the issues. With authors from several continents, this collection is unique in that it focuses on labour regulation in poor and middle-income countries rather than industrialised ones, therefore making it a significant contribution to the field.